Prognostic significance of survivin in rectal cancer patients treated with surgery and postoperative concurrent chemo-radiation therapy - Il Yu, Jeong (Oncotarget, 2016)
BACKGROUND & AIMS: This study is designed to investigate the expression of survivin and p53 in human rectal cancer tissues and analyze associations between expression and clinical outcomes in terms of disease recurrence and survival duration. RESULTS: During follow-up (median 119.0, range 6.6 to 161.3 months), tumor recurrence was detected in 50 patients (43.1%), and local recurrence developed as a first failure site in 13 patients (11.2%). Positive immunostaining of nuclear and cytoplasmic survivin was observed in about one quarter of patients, and about half of all patients had positive staining for p53. Both survivin and p53 were significant prognostic factors of disease-free survival in the univariate analyses, but only survivin remained a significant prognostic factor in the multivariate analysis. METHODS: We performed a retrospective study with 116 locally advanced rectal cancer patients who underwent total mesorectal excision (TME) followed by postoperative concurrent chemo-radiation therapy (CCRT). Immunohistochemical staining was conducted using antibodies for survivin or p53, and their expression was analyzed using an individual score that combined the percentage of positive cells and staining intensity. CONCLUSIONS: Overexpression of nuclear and cytoplasmic survivin in locally advanced rectal cancer patients was associated with a higher recurrence rate in rectal cancer patients treated with TME followed by postoperative CCRT.